Sistem Drainase Terpadu Berwawasan Lingkungan (Ecodrain) pada Kawasan Permukiman di Kelurahan Pelambuan Kecamatan Banjarmasin Barat Kota Banjarmasin - Eka Purnamasari; Robiatul Adawiyah; Akhmad Gazali (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Pelambuan is a sub-district in West Banjarmasin, Banjarmasin City, South Kalimantan Province. Part of the Pelambuan area is still a slum area because there is no drainage, garbage problems, sanitation, etc. So it needs awareness and the role of community members to love the environment and live healthily. Thus, the residents must be given an understanding of the integrated environmental drainage system (ecodrain) in residential areas to maintain and create a healthy environment. In principle, ecodrain is a program to restore and improve the quality of urban drainage flow from pollution caused by garbage or wastewater due to the indiscipline of urban residents who throw garbage or wastewater into channels or rivers that cross urban areas. Handling of drainage, which is carried out in an integrated manner by handling waste and wastewater with an environmentally sound concept (ecodrain), can be carried out in the following ways: installation and operation of waste filters, application of proper waste management with the 3R approach (Reduce, Reuse & Recycle) community-based, community-based sanitation improvement (Sanimas), river water quality restoration through bioremediation, construction of rainwater catchment wells to reduce the volume of rainwater runoff that will flow into drainage channels and rivers.